Development of grain drink technology based on unsteamed buckwheat - G. M. Kerimova; I. A. Fomenko; A. R. Pivchenko; I. R. Sokolov (Новые технологии, 2023)
Herbal drinks are products that have already become familiar to supporters of a «dairyfree  » diet, vegetarians and people with lactase deficiency. There is a wide range of drinks on the market,  among them the most popular types are cereals, legumes, nuts. It is difficult to find a worthy replacement  for cow milk due to the specific organoleptic indicators of raw materials, the content of certain  components that cause allergies or intolerance when they are used. As a substrate for the research, green  buckwheat has been chosen, which does not contain gluten, has a rich biochemical composition and is a  hypoallergenic product. Unlike heat-treated cereals, unsteamed cereals retain more functional  components in their composition. The article proposes a method for obtaining a lactose-free and glutenfree  vegetable drink based on unsteamed buckwheat. The aim of the research is to select the parameters  for the production of a grain drink. The rational concentration of the introduced substrate and the dosage  of enzyme preparations of maltogenic amylase and α-amylase have been determined. Taking into account  the features characteristic of the hydrolysable raw materials, the parameters of enzymatic hydrolysis with  a minimum temperature effect and holding time have been proposed. In the research amylolytic enzymes  from Novozymes (Denmark) and Sibbiopharm (Russia) have been used to reduce the viscosity of a highstarch  substrate, which complicates the technological process of producing a vegetable drink, and to  create the desired organoleptic indicators. In the finished drink, the final indicators of the content of  protein, fat, reducing substances, dry substances have been detected. The finished product is also a source  of soluble dietary fiber, which has a positive effect on the human microbiome.